2020
DOI: 10.1016/j.ijheh.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Residential green space and seasonal distress in a cohort of tree pollen allergy patients

Abstract: Background: Residential green space may improve human health, for example by promoting physical activity and by reducing stress. Conversely, residential green space may increase stress by emitting aeroallergens and exacerbating allergic disease. Here we examine impacts of exposure to residential green space on distress in the susceptible subpopulation of adults sensitized to tree pollen allergens. Methods: In a panel study of 88 tree pollen allergy patients we analyzed self-reported mental health (GHQ-12), per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Studies on adults are less common. A previous study in Northern Belgium found that adults sensitized to tree pollen experienced mental health benefits from residential exposure to green, despite their tree pollen allergy (Aerts et al, 2020). Two Korean studies found contrasting results regarding the protective effects of green space on the prevalence of allergy symptoms in adults (Kim et al, 2020;Kwon et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies on adults are less common. A previous study in Northern Belgium found that adults sensitized to tree pollen experienced mental health benefits from residential exposure to green, despite their tree pollen allergy (Aerts et al, 2020). Two Korean studies found contrasting results regarding the protective effects of green space on the prevalence of allergy symptoms in adults (Kim et al, 2020;Kwon et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…The literature shows that green space can impact the respiratory health of allergy-sufferers significantly. The available studies are limited to either residential exposure (Aerts et al, 2020) or exposure at the administrative region level (Kim et al, 2020). A study of (Jones et al, 2019) found no association between neighborhood natural environment and asthma exacerbation at the level of administrative regions and suggest that future research should assess exposure with more spatial and temporal detail.…”
Section: Introductionmentioning
confidence: 99%
“…However, allergenic plants should be avoided in a home garden as they can be associated with the prevalence of allergy diseases ( 97 ), which will cause more serious mental distress. It has been indicated that exposure to pollen from some allergenic plants is associated with severe allergy symptoms ( 98 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…Ulmer et al (2016) found that urban tree cover was associated with less diagnoses of current asthma. In a previous study in Northern Belgium, we found that adults sensitized to tree pollen experience mental health benefits from residential exposure to green, despite their tree pollen allergy (Aerts et al, 2020b). However, the perceived presence of allergenic tree species was found to be associated with higher mental distress (Aerts et al, 2020b).…”
Section: Introductionmentioning
confidence: 82%